Chronically Elevated Myeloperoxidase Antineutrophil Cytoplasmic Antibody Levels in an Asymptomatic 91‐year‐old Patient. Issue 1 (27th June 2014) - Maeda, Sayako; Yabuuchi, Junko; Ono, Shinya; Makiishi, Tetsuya; Hirose, Kunihiko
Abstract : Myeloperoxidase antineutrophil cytoplasmic antibody (MPO‐ANCA) associated glomerulonephritis is commonly diagnosed in elderly patients with acute kidney injury (AKI). Prompt diagnosis and rapid initiation of appropriate therapy are essential to avoid the development of ANCA‐associated vasculitis, which can be a life‐ and organ‐threatening disease. We report a rare case of a 91‐year‐old male with a high MPO‐ANCA titer, who took allopurinol, and showed no symptoms for >20 months, following which sudden AKI and severe bronchial asthma necessitated hemodialysis and steroid administration. Chronically elevated ANCA titers should be examined for causes and followed up to limit the risk of subsequent disease development.